2020
DOI: 10.1001/jamanetworkopen.2020.7213
|View full text |Cite
|
Sign up to set email alerts
|

Association of Independent Prognostic Factors and Treatment Modality With Survival and Recurrence Outcomes in Breast Cancer

Abstract: This prognostic study identifies independent clinical and molecular measurements associated with overall and recurrence-free survival by homogeneous treatment in patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
(83 reference statements)
4
15
0
Order By: Relevance
“…As in our study, Nguyen et al observed, on 956 patients treated in hospitals of four geographical regions of the United States, an increased risk of mortality with increasing age, except for patients younger than 40 years [33].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As in our study, Nguyen et al observed, on 956 patients treated in hospitals of four geographical regions of the United States, an increased risk of mortality with increasing age, except for patients younger than 40 years [33].…”
Section: Discussionsupporting
confidence: 85%
“…The following factors: tumor size, presence and number of positive lymph nodes, high-grade, hormonal and chemo-therapy were found to influence relapse free survival (LRRFS, DRFS, DFS, OS), an observation similar to that of other studies with a large number of patients [18,19,33].…”
Section: Discussionsupporting
confidence: 83%
“…The reasons for these differences are most probably the different molecular characteristics related to the molecular subtypes. A recent study investigating clinical prognostic factors including TP53 status, grade, size, node positivity, ER and HER2 status, and age found that only nodal status was significantly associated with chemotherapy outcomes [36] . Combined, these results suggest that ultimately molecular and not clinical features will enable the prediction of response for chemotherapy in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, consistent results across studies are lacking, warranting further research on the subject before molecular biomarkers can be useful in selecting patients with NSCLC and being included in treatment algorithms for antiangiogenic agents. However, important advances are being made in other cancer types, including breast cancer, in which a recent study has found an association of independent prognostic factors with specific treatments and has weighted them by the outcome category (51).…”
Section: Discussionmentioning
confidence: 99%